TANGGUNG JAWAB PEMERINTAH KABUPATEN SUMENEP TERHADAP PENGGUNAAN TANAH MASYARAKAT UNTUK PEMBANGUNAN SEKOLAH MENURUT UNDANG-UNDANG NO 2 TAHUN 2012 TENTANG PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM - Anggita Yulia; Ahmad Suryono (Empat Sembilan Publisher, 2026)
Land acquisition for public purposes, particularly in the education sector, often raises legal issues related to the protection of community land rights. This study aims to analyze the legal responsibility of the Sumenep Regency Government in the use of community land for school development based on Law Number 2 of 2012 concerning Land Acquisition for Public Interest, as well as to examine the legal consequences arising from improper land use. This research employs a normative juridical method with a statute and conceptual approach, supported by the analysis of relevant laws, legal principles, and doctrines. The results indicate that, although land acquisition has been clearly regulated, its implementation in practice does not always comply with legal procedures, particularly in terms of providing fair and proper compensation. In certain cases, land owned by the community has been utilized without following formal acquisition mechanisms, leading to disputes and potential violations of legal norms. The study concludes that the government bears legal responsibility for ensuring the protection of land rights through lawful procedures and fair compensation. Failure to do so may result in legal consequences, including claims of unlawful acts by the government and disputes before the administrative or general courts. The implications of this research highlight the importance of strengthening accountability, transparency, and legal compliance in land acquisition processes to ensure the realization of justice, legal certainty, and public welfare.